Inter‐individual and intra‐individual variation of the effects of pulsed RF EMF exposure on the human sleep EEG. Issue 3 (17th February 2015) - Lustenberger, Caroline; Murbach, Manuel; Tüshaus, Laura; Wehrle, Flavia; Kuster, Niels; Achermann, Peter; Huber, Reto
Abstract : Pulse‐modulated radiofrequency electromagnetic fields (RF EMF) can alter brain activity during sleep; increases of electroencephalographic (EEG) power in the sleep spindle (13.75–15.25 Hz) and delta‐theta (1.25–9 Hz) frequency range have been reported. These field effects show striking inter‐individual differences. However, it is still unknown whether individual subjects react in a similar way when repeatedly exposed. Thus, our study aimed to investigate inter‐individual variation and intra‐individual stability of field effects. To do so, we exposed 20 young male subjects twice for 30 min prior to sleep to the same amplitude modulated 900 MHz (2 Hz pulse, 20 Hz Gaussian low‐pass filter and a ratio of peak‐to‐average of 4) RF EMF (spatial peak absorption of 2 W/kg averaged over 10 g) 2 weeks apart. The topographical analysis of EEG power during all‐night non‐rapid eye movement sleep revealed: (1) exposure‐related increases in delta‐theta frequency range in several fronto‐central electrodes; and (2) no differences in spindle frequency range. We did not observe reproducible within‐subject RF EMF effects on sleep spindle and delta‐theta activity in the sleep EEG and it remains unclear whether a biological trait of how the subjects' brains react to RF EMF exists. Bioelectromagnetics. 36:169–177, 2015. © 2015 Wiley Periodicals, Inc.